Atypical hydrocephalus in an Angus herd in Missouri, USA. Issue 4 (23rd October 2017) - Melendez, Pedro; Volkmann, Dietrich; Pithua, Patrick
Abstract : An atypical hydrocephalus case from a 24‐month‐old Angus heifer was diagnosed after a caesarean section was performed. The cow was euthanased after she fell twice during the surgery before having the opportunity to exteriorise the uterus. The fetus was removed from the dam post euthanasia. This teratogenic abnormality resembled a new genetic condition diagnosed in 2009 in the Angus breed called neuropathic hydrocephalus (recessive gene). The calf and dam were not sampled, but the bull, coming from a commercial Angus farm, tested positive for this gene. This case reinforces the importance of a consistent diagnostic methodology when genetic diseases are suspected.